DISTURBING THE PEACE Gender, journalism and the Cypriot press - Bailie, Mashoed; Azgin, Bekir (Routledge Journals, Taylor & Francis Ltd, 2011)
This article explores the structures of both the Greek Cypriot and Turkish Cypriot press in Cyprus in order to consider the role that gender plays in the construction and distribution of knowledge in Cypriot society. The question is whether columns published across the ideological spectrum in both the Turkish Cypriot and Greek Cypriot daily press challenge preconceived notions of gender in the broader communities or whether they reproduce and reinforce previously held patriarchal views of the roles of men and women as citizens in Cyprus. Such views, it is argued, have systematically marginalized women from visible participation in offering alternative futures for the Cypriot communities in Cyprus and relegated them to the position of secondary agents who more often than not play the role of bringing to fruition the imaginings of their male counterparts.
Keywords: conflict; Cyprus; gender; Greek Cypriot; journalist; negative peace; Turkish Cypriot